Isolation and Identification of Protein Spike (Protein-S) in Field Isolates of Infectious Bronchitis Virus - Rahmahani, Jola; Pradhita, Dewanggi Kristi Sasmi; Widjaja, Nanik Sianita; Suwarno, Suwarno (Jurnal Medik Veteriner, 2021)
Infectious Bronchitis (IB) is disease causes great economic impact across nations. Spike protein (protein-S) is one of structural protein of Infectious Bronchitis Virus (IBV) located on enveloped of the virion. Molecular characterization of IBV could be conducted use Sodium Dodecyl Sulphate-Polyacrylamide Gel Electrophoresis (SDS-PAGE) to reveal the protein weight then confirmed through Immuno-Blotting assay. These methods were conducted to know the molecule weight of field isolate compared to seed vaccine. The results of this study indicate the weight of protein-S of field isolate I-147/11 were 168.21 kDa which was same to protein-S of seed vaccine Massachusset.